Dinamika Pendidikan Tinggi Vokasi Penerbangan Merespon Isu Industri 4.0 - Benny Kurnianto (Forum Dosen Indonesia, 2019)
Talking about human development, the topic that keeps existing in higher education is skill-gap between university and industry. The challenge is getting harder with shifting conditions in the globe including the issue of industrial revolution 4.0. This challenge has an immediate effect on the existence and the development of vocational academy such as Indonesian Civil Aviation Institute. Therefore, this study explores the changes that occur in as Indonesian Civil Aviation Institute as a result of higher education policy in Indonesia. This study uses SWOT analysis to examine the strategies taken by this university to encounter the issue. According to this research, there are dynamic changes in the relation between this university, government, and industry as the outcome of dissimilar interpretation of the issue. References : Ayu, N.A.K. 2018. Peluang Social Innovation dalam Revolusi Industri 4.0: Bagaimana Perkembangannya di Indonesia. Yogyakarta: Forbil Institute Disas, E. P. Link and Match sebagai Kebijakan Pendidikan Kejuruan. Jurnal Penelitian Pendidikan, 18(2), 231-242. Etzkowitz, H., & Leydesdorff, L. 1995. The Triple Helix – University Industry Government Relations: A Laboratory for Knowledge Based Economic Development. EASST Review 14, 14-19. Etzkowitz, H., & Leydesdorff, L. 2000. The Dynamics of Innovation: From National Systems and '‘Mode 2'’ to a Triple Helix of University -Industry - Government relations. Research Policy, 29(2), 109-123. Izzati, MF & Wilopo. 2018. Implementasi Triple Helix Dalam Mendorong Pertumbuhan Industri Kreatif Di Kota Malang Sebagai Upaya Peningkatan Daya Saing Untuk Menghadapi Masyarakat Ekonomi Asean. Jurnal Administrasi Bisnis (JAB)Vol. 55 No. 1 Februari 2018 hal 59-68. McKinsey. 2015. Industry 4.0 How to navigate digitization of the manufacturing sector. England: Stamford Senarath, S. A. C. L., & Patabendige, S. S. J. (2014). Job-education mismatch among the graduates: A Sri Lankan Perspective. Ruhuna Journal of Management and Finance, 1(2), 1-16. UNIDO. Industry 4.0: Opportunities and Challenges of the New Industrial Revolution for Developing Countries and Economies in Transition. Panel Discussion USDA. 2008. SWOT analysis a tool for making better business decisions. United States Department of Agriculture Risk Management Agency.